Recent advances in devices for mechanical thrombectomy. (2nd July 2020) - Blanc, Raphaël; Escalard, Simon; Baharvadhat, Humain; Desilles, Jean Philippe; Boisseau, William; Fahed, Robert; Redjem, Hocine; Ciccio, Gabriele; Smajda, Stanislas; Maier, Benjamin; Delvoye, François; Hebert, Solène; et al.
ABSTRACT: Introduction: Acute ischemic stroke (AIS) secondary to the occlusion of a large intracranial vessel (LVO) is a recognized public health problem. Mechanical thrombectomy (MT) has gained full acceptance: Class A, Level 1 in 2015 after the publication of numerous trials. Further meta-analyses have scrutinized extensively those results and international recommendations and guidelines have been given. Nevertheless, multiple-specific points remain to be clarified and are or will be under investigations. Areas covered: This review of the most recent literature (mostly publications after 2015) will cover the actual common practice for MT, especially focusing on the devices available (and their validation), how they are commonly used, relate the most relevant results, and detail some emerging technologies. Expert opinion: The authors will express their own view on the current practice and emphasize on the areas where questions remain and hypothesize what specific improvements are necessary and prone to occur.